MOTIVASI KERJA ISLAM GURU TIDAK TETAP SEBAGAI PAHLAWAN TANPA TANDA JASA (Fenomenologi pada SMP Swasta Islam di Kota Semarang) - Anisa, Nadia Nuur; Djastuti, Indi (Diponegoro Journal of Management, 2015)
One of the factors that supporting the educational success is teachers. Besides of they have a very important role, teachers also having role as an agents of change. Not only giving universal values for us, teachers also giving moral and religious knowledge. As an important part of the educational process, all of teachers should have standard management and regulations. However, in actual practice of the education system in Indonesia, there are some terms of temporary teachers, who don’t received clarity welfare and employment status yet.Temporary teachers have very minimum welfare and can not be comparared with their heavy duties. This indicates that temporary teachers have job motivation to do that. Islam has the rules of whole human life aspects. One of the rule is learning the job motivation’s regularity. Islam also pays a great attention to the teachers.This research aims to analyze the intrinsic factors which influence job motivation of temporary teachers in Islamic perspective. This research used qualitative methods in which data collection are done with the structured interview. Sample of this research are temporary teachers who have tenure more than three years in Private Islamic Junior High School at Semarang city.The results of this research is job motivation of temporary teachers are influenced by internal motivation factors which attached in them. The factors are consists of value or believe, perception, purpose, expectations, attitude, and ability, that shown in their behavior.